Modern technologies in management of diabetes - Iqbal, Anbreen; Qadir, Muhammad Imran; Asif, Muhammad (Journal of College of Medical Sciences-Nepal, 2017)
Diabetes is not one disease but rather is a heterogeneous group of syndromes characterized by an elevation of fasting blood glucose caused by a relative or absolute deficiency in insulin. The two main types of diabetes occur, type-1 is insulin dependent diabetes mellitus and type-2 is non insulin dependent diabetes mellitus. In type-1 body does not produce insulin and about 10% of all diabetic patients are affected. In type-2 diabetes imbalance of insulin and glucose occur and there are about 90% cases for type-2 diabetes. Gestational diabetes is also a type of diabetes and it is found mostly in women’s who are pregnant later such women’s are affected with type-2 diabetes and about 40% cases are studied. Different countries are affected at high level from diabetes. For the treatment of diabetes different techniques like insulin injection, oral vaccination, pancreas transplantation, transplantation of encapsulated islet cells, gene therapy technique and islet cell transplantation are used. All techniques have some advantages and disadvantages, but the encapsulated islet cell transplantation technique is promising with minimum complications.